Dark tourism, “Netflix tourism”: stakes and conflicts of actors in Medellin - Camille Beauvais (Via@)
In Medellin, private actors have seized one of the bloodiest periods in the history of Colombia and a very particular tourism is unfolding around the figure of Pablo Escobar. This tourism development boosted by narco-fictions causes tensions and highlights the challenges of a society’s relationship to its past.